Fractional Sliding Mode Harmonic Control of an Active Power Filter - Wesley Fei; Mingang Hua (Applied Sciences, 2023)
A sliding mode control (SMC) strategy with a fractional-order scheme is developed to provide an effective way to compensate for the harmonic current and strengthen the performance of an active power filter (APF). The formulation of a fractional-order sliding mode controller (FOSMC) is incorporated in the current control of an APF control system, obtaining an extra degree of freedom over integer-order ones to improve the dynamic property. The simulation results of the APF utilizing the designed strategy confirm the satisfactory performance and smaller total harmonic distortion (THD) by comparative study.